2018
DOI: 10.3233/jad-180098
|View full text |Cite
|
Sign up to set email alerts
|

Role of Blood-Brain Barrier in Alzheimer’s Disease

Abstract: The blood-brain barrier (BBB) is involved in the pathogenesis of Alzheimer's disease (AD). BBB is a highly selective semipermeable structural and chemical barrier which ensures a stable internal environment of the brain and prevents foreign objects invading the brain tissue. BBB dysfunction induces the failure of Aβ transport from brain to the peripheral circulation across the BBB. Especially, decreased levels of LRP-1 (low density lipoprotein receptor-related protein 1) and increased levels of RAGE (receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(182 citation statements)
references
References 127 publications
3
179
0
Order By: Relevance
“…AD2 is linked to gliogenesis and cell motility. N8 is involved in gap junction, which supports the assumption that gap junction associated with blood brain barrier may be disrupted in AD to allow the access of virus or bacteria to AD brain (Cai et al, 2018;Devanand, 2018;Montagne et al, 2017;Readhead et al, 2018).…”
Section: Levelssupporting
confidence: 66%
“…AD2 is linked to gliogenesis and cell motility. N8 is involved in gap junction, which supports the assumption that gap junction associated with blood brain barrier may be disrupted in AD to allow the access of virus or bacteria to AD brain (Cai et al, 2018;Devanand, 2018;Montagne et al, 2017;Readhead et al, 2018).…”
Section: Levelssupporting
confidence: 66%
“…In fact, EVs shed from CNS neurons and glia can be found in peripheral blood and in tears [44,205], particularly when inflammatory mediators activate CNS endothelia, enhancing BBB permeability [206,207]. In this regard, it has been observed that the permeability of the BBB is increased in neurodegenerative conditions such as Alzheimer's disease, vascular dementia, and multiple sclerosis [45,[208][209][210]. Furthermore, systemic inflammation increases BMEC permeability and modulates BBB functions [207,211,212].…”
Section: Evs and The Blood-brain Barriermentioning
confidence: 99%
“…Neurodegenerative diseases such as AD are complex multifactorial pathologies, emerging from a multitude of alterations that include oxidative stress, protein aggregation, energetic failure, synaptic dysfunction and inflammation, which ultimately lead to cell death in specific brain regions . Disruption of iron homeostasis and consequently its accumulation has been associated with the pathogenesis of neurodegenerative disorders, such as Parkinson's disease (PD) and AD .…”
Section: Introductionmentioning
confidence: 99%
“…15 Neurodegenerative diseases such as AD are complex multifactorial pathologies, emerging from a multitude of alterations that include oxidative stress, protein aggregation, energetic failure, synaptic dysfunction and inflammation, which ultimately lead to cell death in specific brain regions. 17,18 Disruption of iron homeostasis and consequently its accumulation has been associated with the pathogenesis of neurodegenerative disorders, such as Parkinson's disease (PD) and AD. 19 Recently, it was suggested that exposure to high levels of iron during childhood increases susceptibility to neurodegenerative diseases such as PD and AD in elderly, considering a "window of vulnerability" in which, during the first 2 years of life, the blood-brain-barrier is more accessible to iron levels in the periphery leading to iron over storage in the brain.…”
mentioning
confidence: 99%